Piston reactor for chemical energy storage: Modeling study to explore electro-mechanical conversion route using propane feedstock - Aya Abousrafa (17542485) (2024)
Within the context of renewables and chemical energy storage, this work aims to explore chemical reaction conversion through the electro-mechanical route which is different from the commonly employed electro-thermal and electro-chemical conversion methods. Piston reactor is a novel equipment concept that can couple the rotational movement from an electric motor to a reciprocating piston within an enclosed reaction chamber resembling the operation of an internal combustion engine. Exploration of a reactor technology still in the laboratory stage requires an assessment of reaction intermediate mixtures to identify potential leads. This work uses a systematic methodology to assess these intermediate mixtures beyond typical reactor yield metrics to include economic values as part of the decision-making toward identifying lead candidates. Rather than focusing on a specific target reaction or product, this work is carried out as a model-driven study to cover a wider range of conditions and product scenarios. Propane as the main feedstock is selected because it is easier to trigger in the piston reactor, it is not a complex feed, a detailed kinetic mechanistic model is available to study it, and most importantly it can generate a wide range of industrially relevant products to serve the purpose of this study. The study revealed that the highly endothermic propane pyrolysis reaction requires intake temperatures larger than 950 K which is impractical. Diluting the feed with argon is one way to lower this intake temperature and achieve desirable conversion. This however is impractical because of additional separation steps and reduced production capacity. Thermal coupling of propane pyrolysis with exothermic side reactions by co-feeding oxygen, water, or carbon dioxide are investigated and showed promising results. A diverse range of products are produced such as hydrogen, carbon monoxide, ethylene, and propylene, achieving high conversions (>90 %), while simultaneously generating useful work and process heat. Unconventional triggers such as using ozone to generate radicals and trigger ignition are investigated to further lower the intake temperature requirements. The explored solution space is then evaluated considering a new reactor metric as the value of products mixture stream. Regions of high-value products do not match those obtained using the traditional yield metrics. This shows the importance of what metrics to use for assessing reactors with wide range of reaction mixture intermediates as the piston reactor. Full economic analysis and optimization are the right direction in the future to properly assess the potential of piston reactor technology. Other Information Published in: Chemical Engineering and Processing - Process Intensification License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cep.2024.109840